2005
DOI: 10.1002/chem.200500339
|View full text |Cite
|
Sign up to set email alerts
|

Camouflaged Carborarods Derived from B‐Permethyl‐1,12‐diethynyl‐para‐ and B‐Octamethyl‐1,7‐diethylnyl‐meta‐carborane Modules

Abstract: Rigid camouflaged carborarods constructed from the corresponding C,C'-diethynyl derivatives of B-decamethyl-1,12-dicarbadodecaborane(12) (6) and B-octamethyl-1,7-dicarbadodecaborane(12) (48) have been synthesized by largely conventional organic transformations. These carborarods are the longest discrete rod species available by this method in which B-methylated p-carborane and m-carborane cages are linked through their carbon vertices by using butadiynylene moieties. They exhibit enhanced solubility in common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 101 publications
(44 reference statements)
1
31
0
1
Order By: Relevance
“…The overall yields of 1, 2, 6 and 7 from para-carboranes 3 and 5 are 69%, 67%, 63% and 48%, respectively, which are superior to reported yields of up to 26% from previous single/two-step syntheses [6][7][8]10]. The convenience of a two-step route is also an obvious advantage in effort and cost over the more elaborate multi-step syntheses, which afford the ethynyl carboranes in comparable yield to those described here [9].…”
Section: Resultssupporting
confidence: 63%
See 3 more Smart Citations
“…The overall yields of 1, 2, 6 and 7 from para-carboranes 3 and 5 are 69%, 67%, 63% and 48%, respectively, which are superior to reported yields of up to 26% from previous single/two-step syntheses [6][7][8]10]. The convenience of a two-step route is also an obvious advantage in effort and cost over the more elaborate multi-step syntheses, which afford the ethynyl carboranes in comparable yield to those described here [9].…”
Section: Resultssupporting
confidence: 63%
“…A low-yielding synthesis of 2 has been reported by Kaszynski et al [8] while we have also used 1-bromo-3-methyl-1-butyn-3-ol instead of 4 in a two-step synthesis of 1 in low yields [7]. Herzog et al reported multi-step syntheses of 1 and 2 from 3 in overall yields of 64% [9]. These yields are considerably improved with respect to the simple two-step syntheses from 1 and, whilst elegant, the complete synthetic procedure is somewhat tedious.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Their application in coordination chemistry is especially promising, as suggested by a comparison to related compounds: (i) dicarbacloso-dodecaboranes with ethynyl groups bonded to the cluster carbon atoms have been successfully used as ligands, [2,25,27,29,46] for example, in [{Ru(dppe)Cp*} 2 {µ-1,12-(CϵC) 2 -closo-1,12-C 2 B 10 H 10 }] [27] (dppe = 1,2-bis(diphenylphosphanyl)ethane) and (ii) 9,12-(HCC) 2 -closo-1,2-C 2 B 10 H 10 (1a) as well as 9,10-(HCC) 2 -closo-1,7-C 2 B 10 H 10 (3a) reveal structural similarities to 1,2-diethynylbenzene that has proven to be a versatile bridging ligand, for example, in metallamacrocycles. [47] Furthermore, with the ethynyl-functionalized carba-closo-dodecaborate anions [12-HCC-closo-1-CB 11 -, isoelectronic anionic counterparts [33,48] are available for comparative studies.…”
Section: Resultsmentioning
confidence: 99%